Etching of Blood Proteins in the Early and Late Flowing Afterglow of Oxygen Plasma. Issue 1 (18th October 2013) - Vesel, Alenka; Kolar, Metod; Recek, Nina; Kutasi, Kinga; Stana‐Kleinschek, Karin; Mozetic, Miran
<x xml:space="preserve">Abstract</x> Films of proteins fibrinogen and albumin are exposed to neutral reactive particles in order to study their etching rates in early and late oxygen afterglows of microwave plasma. The etching rates are determined at different pressures between 50 and 400 Pa. The etching rates for both proteins first increase with the increasing pressure, while later they reach a constant value. Furthermore, the etching rates are higher in the early than in the late afterglow. The concentration of all available species in the afterglow, i.e. neutral oxygen atoms in the ground state, neutral molecules in the first excited state, and ozone is determined either by experimental measurements or theoretically using a well‐established model. The etching rates are explained by the synergistic effects of atoms and metastable molecules.<inline-graphic xlink:href="ark:/27927/pgg3zvzmqss" content-type="ppap201300067-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />